The effect of sustainable shipping practices on shippers’ loyalty : the mediating role of perceived value, trust and transaction cost - Yuen, Kum Fai (2018)
This study investigates the role of perceived value, trust, and transaction cost in mediating the effect of sustainable shipping practices (SSP) on shippers’ loyalty. Theoretical and alternative models were proposed and compared using survey data collected from 289 shippers. The results show that the relationship between SSP and shippers’ loyalty is mediated by shippers’ perceived value of SSP, shippers’ trust towards a shipping company’s commitment towards sustainability, and sustainability-related transaction cost. This study offers an alternative theoretical explanation to the relationship and provides important managerial insights to strengthen shippers’ loyalty through implementing SSP.